The influence of Organizational Commitment and the quality of library services on the University Students’ Reading Interest - et. al., Ismet Sulila, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The low reading interest of university students has been identified as a problem in human resource development as it hampers them to broaden their knowledge. Additionally, reading is no longer becoming their primary need. This research is essential to find out whether or not the organizational commitment and service quality impact the university students’ reading interest either partially or simultaneously. The research employs a quantitative method with ex post facto approach. The research finding elucidates how the organizational commitment and service quality impact the university students’ reading interest either partially or simultaneously. The implication of finding covers: 1) enhancing commitment in performing various service tasks, 2) enhancing service quality, growing caring attitude to visitor, adding librarycollection, and improving facility and infrastructure, and 3) attempting various innovative programs to attract students’ reading interest and preparing digital service in accordance with the need of advancement in science and technology.